2018
DOI: 10.1016/j.freeradbiomed.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

B2-Lymphocyte responses to oxidative stress-derived antigens contribute to the evolution of nonalcoholic fatty liver disease (NAFLD)

Abstract: Recent evidence implicates adaptive immunity as a key player in the mechanisms supporting hepatic inflammation during the progression of nonalcoholic fatty liver disease (NAFLD). In these settings, patients with NAFLD often show an increase in the circulating levels of antibodies against oxidative stress-derived epitopes (OSE). Nonetheless, the actual role of humoral immunity in NAFLD is still unclear. This study investigates the contribution of B-lymphocytes to NAFLD evolution. B-lymphocyte immunostaining of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
133
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(150 citation statements)
references
References 45 publications
6
133
0
1
Order By: Relevance
“…These findings are supported by clinical observations that both paediatric and adult patients with NASH are characterized by an increase in levels of liver and circulating IFNγ-producing CD4 + T cells 36,37 . Moreover, in adult patients with NASH, plasma IFNγ levels positively correlate with the number and size of hepatic lymphocyte aggregates as well as with the severity of fibrosis 27 . In response to inflammatory stimuli, CD4 + T cells can also differentiate to type 17 T helper (T H 17) cells, which are characterized by the expression of the nuclear receptor retinoic acid-related orphan receptor-γt and by the production of IL-17 and, to a lesser extent, IL-21, IL-22, IFNγ and TNF 38 .…”
Section: Role Of Cd4 + T Helper Cells the Recruitment Of Cd4 +mentioning
confidence: 95%
See 2 more Smart Citations
“…These findings are supported by clinical observations that both paediatric and adult patients with NASH are characterized by an increase in levels of liver and circulating IFNγ-producing CD4 + T cells 36,37 . Moreover, in adult patients with NASH, plasma IFNγ levels positively correlate with the number and size of hepatic lymphocyte aggregates as well as with the severity of fibrosis 27 . In response to inflammatory stimuli, CD4 + T cells can also differentiate to type 17 T helper (T H 17) cells, which are characterized by the expression of the nuclear receptor retinoic acid-related orphan receptor-γt and by the production of IL-17 and, to a lesser extent, IL-21, IL-22, IFNγ and TNF 38 .…”
Section: Role Of Cd4 + T Helper Cells the Recruitment Of Cd4 +mentioning
confidence: 95%
“…1). Interestingly, the size and prevalence of these aggregates positively correlate with lobular inflammation and fibrosis scores 27 . Hepatic infiltration by B cells and CD4 + and CD8 + T cells is also evident in different experimental models of NASH, in which it parallels with worsening parenchymal injury and lobular inflammation 29-33 . These T cells express the memory or effector markers CD25, CD44 and CD69, along with enhanced production of the cytokine LIGHT (also known as TNFSF14), indicating their functional activation 29,30,33 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 In recent years, increasing studies have suggested that B lymphocytes are also involved in adipose tissue inflammation. 16 However, the role of B lymphocytes in the inflammation of MAT is poorly understood. 14 Transferred B2 cells in EAT of HFD-fed mice to HFD-fed B null recipient mice result in increased adipose tissue inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…15 B null mice show improved insulin resistance and glucose metabolism compared to control mice under the stimulation of HFD, 14,15 and B2 cell depletion in mice resulted in alleviated NAFLD. 16 However, the role of B lymphocytes in the inflammation of MAT is poorly understood. Here, we aimed to explore the role of MAT B cells in MAT inflammation.…”
Section: Introductionmentioning
confidence: 99%